Deprivation Index for Small Areas Based on Census Data in Argentina - Durán, Rodrigo Javier (2017)
This paper presents the construction and estimation of a deprivation index based on Principal Factors Analysis for the 2010 Argentina Population and Housing Census in a census tract level. From the application of PFA were estimated two factors, one related to material and the other to social deprivation aspects. Based on the material deprivation factor, a synthetic General Deprivation Index (GDI) has been calculated. In addition, a Deprivation Emergency General Index (DEGI) was defined and measured. The DEGI prioritize the implementation of local development policies over small rural or urban areas according to the greater number of inhabitants in relation to the urban or rural total for a Department of Argentina. The factors and the GDI indicator has been validated the Kaiser–Meyer–Olkin scores were greater than 0.7 for urban, rural, and total tracts, the Cronbach’s alpha coefficient for the material factor was 0.811 and the Pearson’s correlation coefficient between GDI and the Unsatisfied Basic Needs index was 0.659. The index estimates were mapped on QGIS, a Geographic Information System. The intensity and composition of the deprivation were different according to the geographic areas of Argentina; the lowest values of deprivation correspond to the central zone of the country and its urban areas, which is related to inequalities in the economic growth between urban and rural spaces. Finally, it is expected that this new index will be useful for the formulation and evaluation of public development policies for urban and rural areas in Argentina.